DEMOCRATIC DESIGN: SOCIAL ORIENTATION OF CITY PLANNING AND INTERACTION PROBLEMS - Darya Alexandrovna Parshukova; Evgeny Vladimirovich Galdin (Современная наука и инновации, 2022)
The article is devoted to participated design - one of the tools for the development of the urban environment, which is attended by all stakeholders in the project: local residents, community, urban activists, as well as representatives of business and administrative structures